An experimental study on shear behaviour of fully grouted rock bolt under static and dynamic loading conditions. (February 2023) - Khaleghparast, Saman; Aziz, Naj; Remennikov, Alex; Anzanpour, Sina
Graphical abstract: Highlights: Internal confinement of the concrete eliminates premature axial and radial cracking. If premature crack eliminated, rockbolt failure can be in more shear than tension. Double shear apparatus setup subject to high velocity impact load. Dynamic shear capacity of rock bolt is 70 % of its static shear capacity. Abstract: This paper aims to enhance the understanding of conventional rock bolt performance subjected to shear loading under static and in particular dynamic loading conditions. For this purpose, thirteen sets of static tests were undertaken using 16 mm smooth and 18 mm ribbed rock bolts aiming; 1) to examine the effect of internal confinement, and 2) to evaluate the energy absorption of the system subjected to static shear loading. The dynamic response of the conventional 18 mm ribbed rock bolt was assessed by using the drop hammer to generate high-intensity dynamic loading. The results showed that using perforated steel tubes inside concrete blocks as internal confinement in the vicinity of the shear planes prevents axial as well as radial cracking in the concrete, which enabled the rock bolt to go through more shear rather than tension. Furthermore, the shear performance of the conventional rock bolt under high-velocity impact load was found to be 70 % of that in static loading conditions, which tallies well with past experimental studies as well as mathematical approaches.